Evaluation of the Enzymatic Hydrolysis of Wet White Assisted with Ultrasound to Obtain Hydrolyzed Collagen - Almonacid-Jiménez, Leidy Yaneth; Vallejo-Rodríguez, Juan Sebastián; Agudelo-Valencia, Rafael Nikolay; Hernández-Fernández, Javier Adolfo; Ortiz-Medina, Óscar Leonardo; Ovalle-González, Diana Paola (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The present investigation focuses on the evaluation of the enzymatic hydrolysis method assisted by ultrasound in obtaining hydrolyzed collagen from the use of the residue (wet white) from leather tanned with glutaraldehyde, in order to minimize the generation of environmental impacts that have occurred for such material. The effect of pH of the solution, enzyme dose, intensity of applied ultrasound, and temperature of the mixture were evaluated, keeping constant the initial mass of wet white, volume of water and reaction time. The experimental results indicate that for pH 9 doses of enzyme Tan G Plus 0.00012 kg, temperature of 313.15 K and intensity of ultrasound of 40 % it is possible to degrade the material and denature the protein, obtaining a hydrolyzed collagen weight concentration of 3.013 kg / m3, for each kilogram of material used, which represents a 3.0% mass recovery of wet white. It is observed that the most representative variables for the analyzed process are the pH and the temperature, giving a higher performance to the process allowing get a higher amount of hydrolyzed protein.